Sensitive Determination of Water Insoluble Dyes Used as Marking of Commercial Petroleum Products Using High-Performance Liquid Chromatography with Electrochemical Detection - Goncalves Trindade, Magno Aparecido [UNESP]; Zanoni, Maria Valnice Boldrin [UNESP]; Matysik, Frank-Michael (Wiley-v C H Verlag Gmbh, 2010)
This paper describes an analytical method using high-performance liquid chromatographic (HPLC) separation coupled with electrochemical detection to detect three dyes, Solvent Blue 14 (SB-14), Solvent Blue 35 (SB-35) and Solvent Red 24 (SR-24). The dyes were eluted and separated using a reversed-phase column (C-8) under isocratic elution with the mobile phase containing a mixture of acetonitrile/ammonium acetate (5.0 mmol L(-1)) at the ratio of 75:25 (v/v). Two sample pretreatment methods were tested and successfully applied to quantify SB14, SB-35 and SR-24 dyes in gasoline samples. The proposed method was simple, fast and suitable to detect and quantify marker dyes in gasoline sample at low concentration.
Keywords: Solvent dyes; Marker dyes; Petrol sample; Fuel; Electrochemical detector; Liquid chromatography; Dyes